Autoimmune inflamatory syndrome induced by adjuvants (silicone breast implants and lip fillers) - Pocevski, Božidar P; Pavlov - Dolijanović, Slavica (Medicinski podmladak, 2021)
Introduction: Silicone breast implants (SBI) have been used since 1962. in the reconstruction of post-mastectomy cases, in augmentation of the breast, or for cosmetic purposes, and fillers with biopolymer (FB) have been used since the 1990s. Today, they are considered as adjuvants of the immune system. Most complications of SBI and FB are local in nature, but some patients experience systemic symptoms, which is defined as adjuvant-induced autoimmune inflammatory syndrome (ASIA). Aim: The aim of this study is to demonstrate the possible association of silicone breast implants and FB with the development of immune-mediated inflammatory rheumatic diseases (IMIRD). Material and methods: The research represent retrospective study which involved 15 women patients with immune-mediated inflammatory rheumatic diseases, 6 of whom were patients with implanted silicone breast implants for cosmetic reasons, and 9 patients with placement of fillers with biopolymer on the lips. Results: The average time from silicone implantation to the onset of the first symptoms was 6.10 ± 5.3 (range 6 months to 24 years). The following immune-mediated inflammatory rheumatic diseases were recorded: 3 patients with systemic sclerosis (SSc), 3 patients with undifferentiated arthritis, 3 patients with seropositive rheumatoid arthritis, 1 patient with systemic lupus erythematosus, 2 patients with undifferentiated SCTD, 2 patients with mixed connective tissue disease, and one patient with unexplained systemic disease. Seven patients had the Raynaud phenomenon. Spontaneous abortions were reported in 2 patients. Conclusion: Earlier reports that silicone breast implants and biopolymer fillers are safe today are changing with the description of ASIA syndrome.